Alcohol Use and Experiences of Partner Violence Among Female Sex Workers in Coastal Andhra Pradesh, India. (March 2019) - Heylen, Elsa; Shamban, Emily; Steward, Wayne T.; Krishnan, Gopal; Solomon, Raja; Srikrishnan, A. K.; Ekstrand, Maria L.
This cross-sectional study describes the prevalence and context of violence by sexual partners against female sex workers (FSWs, N = 589) in Andhra Pradesh and its association with alcohol use by FSWs and abusive partners. In all, 84% of FSWs reported alcohol use; 65% reported lifetime physical abuse by a sexual partner. Most abused women suffered abuse from multiple partners, often triggered by inebriation or FSW's defiance. In multivariate logistic regressions, frequency of FSW's alcohol use was associated with abuse by clients and primary partner, whereas partner's alcohol use was only significant for abuse by primary partner, not clients.